Challenges in moderating disruptive player behavior in online competitive action games - Kocielnik, Rafal; Li, Zhuofang; Kann, Claudia; Sambrano, Deshawn; Morrier, Jacob; Linegar, Mitchell; Taylor, Carly; Kim, Min; Naqvie, Nabiha; Soltani, Feri; Dehpanah, Arman; Cahill, Grant; et al. (Frontiers in Computer Science, 2024)
Online competitive action games are a very popular form of entertainment. While most are respectfully enjoyed by millions of players, a small group of players engages in disruptive behavior, such as cheating and hate speech. Identifying and subsequently moderating these toxic players is a challenging task. Previous research has only studied specific aspects of this problem using curated data and with limited access to real-world moderation practices. In contrast, our work offers a unique and holistic view of the universal challenges of moderating disruptive behavior in online systems. We combine an analysis of a large dataset from a popular online competitive firstperson action title (Call of Duty®: Modern Warfare®II) with insights from stakeholders involved in moderation. We identify six universal challenges related to handling disruptive behaviors in such games. We discuss challenges omitted by prior work, such as handling high-volume imbalanced data or ensuring the comfort of human moderators. We also offer a discussion of possible technical, design, and policy approaches to mitigating these challenges.